Hopping and Landing Performance in Male Youth Soccer Players: Effects of Age and Maturation - Read, Paul J; Oliver, Jon L.; De Ste Croix, Mark B. A.; Myer, Gregory D.; Lloyd, Rhodri S. (International Journal of Sports Medicine, 2017)
Quantifying hopping and landing performances can assist coaches in identifying young male soccer players who may be at increased risk of injury. The influence of chronological age and maturation on these measures in this population is unknown. Single leg hop for distance (SLHD) and 75% horizontal hop and stick landing force (75%Hop) were examined in a cross-sectional sample (N=400) of elite male youth soccer players. Between-group differences for both chronological age (U11–U18) and stage of maturation (pre-, circa- or post-peak height velocity (PHV)) were analyzed. Absolute 75%Hop increased with both age and maturation. Apart from the U18s, pre-PHV and U11–U12 players displayed the greatest relative landing forces compared to all other groups (p<0.001; d=0.56–0.93). Absolute and relative SLHD were greatest in the U18s and post-PHV players (p<0.001; d=0.35–2.04). A trend showed increased SLHD with each consecutive age group although a reduction in performance was identified in the U13s (d=0.50–0.59). High volumes of accumulated soccer participation in the U18s may lead to altered landing strategies indicative of high injury risk. A temporary reduction in hop performance in the U13s may also be linked to a period of adolescent awkwardness.